(untitled) (Revista Contexto & Saúde, 2026)
Objective: To evaluate the association between sociodemographic and economic factors and levels of Knowledge, Attitude, and Practice (KAP) regarding the use of regional foods by families with children under five years of age in rural Ceará. Method: This is a cross sectional study conducted with 70 mothers residing in the municipalities of Acarape/CE and Redenção/CE between January and March 2023. A sociodemographic questionnaire and the KAP survey were used to assess the domains associated with the use of regional foods. Results: Most participants had inadequate knowledge (82.9%), while 81.4% had an adequate attitude, and 75.7% reported adequate eating practices. There was a statistically significant association between the maternal occupation "housewife" and adequate eating practices (p < 0.05). Multivariate analysis showed that participants informed about nutrition were 26.7% more likely to have adequate knowledge (OR = 0.733, p < 0.05), and mothers with an adequate attitude were 5.4 times more likely to have adequate eating practices (OR = 5.483, p < 0.05). Conclusion: Sociodemographic and economic factors, with an emphasis on occupation and access to information about child nutrition, directly influence KAP in terms of the use of regional foods. These findings reinforce the need for educational strategies and public policies to promote healthy eating in early childhood.